2019
DOI: 10.3846/tede.2019.11261
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Environmental Kuznets Curve. An Investigation on Eu Economies

Abstract: Designing and implementing relevant and effective environmental policies and fostering green and environmental-friendly approaches and behaviors are constant aims for policy makers all over the world. Concurrently, implementing environmental policies involves significant economic and financial efforts, in order to repair environmental damage and to prevent future negative environmental consequences. How effective are the environmental expenditures and how are they related to the economic growth, i.e. the GDP l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Considering the Kuznets environmental curve arguments, empirical studies usually find a positive association between economic growth and pollution emissions. In this context, Badulescu et al [34], Panait et al [35], Squib and Benhmad [22], and Simionescu [28] support the formulated hypothesis.…”
Section: Hypothesis 1 (H1) the Development Of Economic Activity And E...mentioning
confidence: 63%
See 2 more Smart Citations
“…Considering the Kuznets environmental curve arguments, empirical studies usually find a positive association between economic growth and pollution emissions. In this context, Badulescu et al [34], Panait et al [35], Squib and Benhmad [22], and Simionescu [28] support the formulated hypothesis.…”
Section: Hypothesis 1 (H1) the Development Of Economic Activity And E...mentioning
confidence: 63%
“…Furthermore, they found that energy consumption encourages an environmental footprint. Similarly, the empirical research of Badulescu et al [34] found EKC assumptions for EU countries.…”
Section: The Causality Between Economic Growth and Carbon Dioxide Emi...mentioning
confidence: 79%
See 1 more Smart Citation
“…Only then we could favor our choices of products and services less harmful to the environment to effectively implement environmental policies it is demanded higher economic and financial efforts for countries and their national stakeholders. In sum, concerted efforts at all levels are mandatory, from international, national, and regional organizations, governments, and public authorities, to companies (financial and nonfinancial), non-governmental institutions, individuals, and households [90]. If further efforts are still needed in the EU 27, in developing countries it is even more urgent [91] and necessary.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Success in reducing emissions and concentrations of pollutants such as sulfur dioxide in the developed countries in the 1970s and 1980s helped generate the idea of the "environmental Kuznets curve" [51]. With the growth of the gross domestic product (GDP), the state of the environment at the initial stage is rapidly deteriorating, but then a turning point occurs.…”
Section: So X Abatement Technologiesmentioning
confidence: 99%